Effect of Fertilizers on the Yield and Nutrient Uptake by Transplanted Aman Rice (Binadhan-7) Grown in Two Soils of North-West Bangladesh (Journal of Environmental Science and Natural Resources, 2015)
Four field experiments were carried out with Binadhan 7 at Birgonj, Dinajpur; Debigonj, Panchagarh; Kaligonj, Lalmonirhat and Pirgonj, Rangpur during T.aman (kharif II) season of 2011 in the Old Himalalayan Piedmont Plain (AEZ 1) and Tista Meander Floodplain Soils of North-West Bangladesh. The experiments were designed with eight treatments and laid out in randomized complete block design (RCBD) with three replications. The treatment combinations were: T1 (100%STB), T2 (T1 + 25% N), T3 (T1 + 25% NP), T4 (T1 + 25% NK), T5 (T1 + 25% PK), T6 (T1 + 25% NPK), T7 (75% of T1) and T8 (Control). Results indicated that application of different fertilizers significantly affected the grain yield at all of the four locations. The highest grain yield was found in treatment T6 (T1 + 25% NPK). Statistically identical yield was observed in treatments T3, T4 and T5 at Dinajpur; T3 at Panchagar; T2, T3, and T4 at Lalmonirhat and T2 at Rangpur. All the treatment combinations gave significantly higher grain yield over the control at all of the locations. The highest straw yield was found in treatment T6 (T1 + 25% NPK). Statistically identical straw yield was found in T3 and T4 at Dinajpur; T1, T4 and T5 at Panchagar; T2, T4, T5 and T7 Lalmonirhat and all treatments except T7 and T8 at Rangpur. Significantly the lowest yield was obtained in the control treatment (T8) in all of the locations. The highest total N uptake was observed in treatment T6 at all of the four locations. For total P uptake, the similar trend of total N uptake was observed for all the locations. Treatment T6 showed the highest uptake of total K at all locations. The highest uptake of total S was observed in treatment T6 at Dinajpur, Panchagarh and Lalmonirhat. But the highest uptake of total S was observed in treatment T3 at Rangpur. However, the lowest total N, P, K and S uptake was observed in control treatment (T8) at all locations. The partial budget analysis of T.aman rice demonstrated the highest net benefit of tkha-1 85,598/-, 78,619/-, 58,308/- and 72,532/- in T6 treatment followed by tkha-1 76,348/- in T4 treatment, 71,100/- in T3 treatment, 54,192/- in T3 treatment and 68,247/- in T2 treatment where the highest MBCR of 5.40, 3.75, 2.20 and 3.84 was also observed in T6 treatment at Dinajpur, Panchagarh, Lalmonirhat and Rangpur, respectively. Based on most profitable treatments, fertilizer doses of N80P8K40S8Zn1 in Birgonj, Dinajpur; N84P8K40S6Zn1 in Debigonj, Panchagarh; N80P8K40S6Zn1 in Kaligonj, Lalmonirhat and N81P8K35S8Zn1 in Pirgonj, Rangpur could be recommended for higher yield of Binadhan-7 rice in North-West Bangladesh.DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22106 J. Environ. Sci. & Natural Resources, 6(2): 115-120 2013